Locating Reflective Practices: Findings From a Self-Study - Lourdes Zaragoza Mitchel (Networks: An Online Journal for Teacher Research, 2007)
This article reports the findings of an action research project conducted by a group of teachers and professors at a Professional Development School (PDS) in suburban New Jersey. The study’s purpose was 1) to examine whether participation in the PDS activities increased in-service teachers’ reflective practices and 2) to provide the PDS leadership with data on how reflection might be increased throughout the district. Although student learning is the ultimate goal of the PDS partnership, the focus of the study is on teacher reflection as a first step towards improving students’ achievement. The findings speak to the need for teachers to participate in comentoring (Kochan & Trimble, 2000) within an environment that addresses both novice and experienced teachers’ development (Kardos, et al., 2001).